GIS-BASED FUZZY AHP APPROACH FOR SOLAR FARM SITE SUITABILITY ANALYSIS IN EGOR, BENIN CITY, NIGERIA - Oladosu, S. O.; Obayuwana, S. F.; Okoeka, G. E.; Aizesogie, E. O. (FUDMA JOURNAL OF SCIENCES, 2025)
The increasing demand for sustainable energy solutions in Nigeria has necessitated the exploration of alternative energy sources, particularly solar power. This study presents a cost-effective suitability analysis for siting a solar photovoltaic (PV) farm in Egor Local Government Area of Edo State, Nigeria, using an integrated Geospatial Information System (GIS) and Fuzzy Analytical Hierarchy Process (FAHP) framework. Eight critical factors were evaluated: solar radiation, elevation, slope, temperature, relative humidity, land use/land cover, distance to roads, and distance to residential areas. Each factor was standardized using fuzzy membership functions, weighted using the AHP pairwise comparison method, and overlaid using fuzzy summation to generate a final suitability map. Validation was performed by cross-checking spatial outputs with existing physical features and confirming consistency with known land use characteristics. The results reveal that solar radiation and elevation are the most influential criteria, with weighted sums of 5.802 and 3.204, respectively. The analysis identifies Evbuotubu and surrounding zones as highly suitable for solar farm development. This study demonstrates that the combination of GIS and FAHP provides a robust decision-support tool for identifying optimal locations for solar energy infrastructure in urbanizing environments. The findings offer practical insights for policymakers, planners, and energy developers aiming to expand renewable energy infrastructure in Nigeria.